Zeitenwende in German-Chinese trade relations? Evidence from German firms - Andreas Baur; Lisandra Flach (CESifo GmbH, 2024)
The Russian attack on Ukraine in February 2022 marked not only a turning point (Zeitenwende) for German security policy but also for German foreign economic policy. From a European standpoint, the war served as a painful reminder of how economic dependencies can be used as political leverage, bringing the geopolitical dimension of trade relations and economic interdependencies into public focus. In particular, economic ties with the People's Republic of China are increasingly being scrutinized. The ifo Institute conducted a representative survey with German firms in February 2024 to assess changes in their reliance on Chinese inputs since the outbreak of the war and firms' plans regarding their supply relationships with China.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Import; China; Deutschland